Parodic metafiction : an approach to self-reflexive fiction in two works by John Barth - Kofman, Gustavo E. (2015)
The present study aims at elaborating on the connection between two concepts in the field of literary studies, namely metafiction and parody, alongside other related notions, such as the function of irony as a rhetorical mechanism and the use of myths as intertexts. Among the several scholars who address these topics, Rose (1979 and 1993), Hutcheon (1980 and 1985), and Waugh (1984) specifically deal with how these concepts relate to one another. The texts proposed for this study –Perseid and Bellerophoniad, in Chimera (1972) by American author John Barth– share specific rhetorical and narrative elements that allow us to frame this analysis within the theoretical notions referred to before. It has been noted that those theoretical works that address these concepts, as well as the more specific critical studies reviewed, do not deal with precise analytical categories which can embrace the conceptual network that these texts present. An extensive inquiry conducted in the main academic research databases reveals that the problem as stated in this proposal has not yet been investigated and no papers that analyse Barth’s texts from the theoretical perspective outlined here have been found. By constructing a model of textual analysis, this proposal aims at contributing to the study of metafiction and parody and to the critical analysis of metafictional narratives in general. In so doing, this proposal can provide working analytical tools that are likely to be applied to other research studies that incorporate a wider or different variety of literary texts.